Praktik PRAKTIK BAIK TEACHERPRENEURSHIP PADA GURU MI MA’ARIF MALEBO, KANDANGAN, TEMANGGUNG - Agus Ilmi Samudin (STAINU Purworejo, 2023)
This study aims to find out about entrepreneurial activities or what is known as the practice of teacherpreneurship vaik in the MI Ma'arif Malebo Educational Environment with the implementation of teacherpreneurship directly at MI Ma'arif Malebo. This study used qualitative studies whose data were obtained from various observation activities, interviews and hypotheses in the study. In addition, this research approach also uses case and descriptive study studies so that in this study it also aims to analyze the quality of MI ma'arif Malebo teachers applying good teacherpreneuship practices in generating social profits so that aspects of their welfare are more guaranteed, in addition to finding social profits in this study, it is explained that teachers are also expected to be able to improve non-academic competencies other than academics. The subject of this study is in teachers as locomotors driving entrepreneurial activities. This research focuses on the issue of about the hononarium of teachers which is not comparable to what the teachers have been devoted to, the teachers only receive a wage of around Rp.250,000-Rp.500,000 for each of these data from the background of the problem to the theory, concept and practical application of teacherpreneurship are used as the basis of scientific theory so that it can measure the extent of the quality of good practice of teacherpreneurship. In addition, the prodak presented in covering teacherpreneur activities is a conventional system by depositing from warung-kewarung, as well as a digital system by being peddled through marketplaces, one of which is the Shopee application.